Narrativas de padres, madres y cuidadores sobre sexualidad infantil y educación sexual en niños de 4 a 7 años en la ciudad de Bogotá (2024)
The present project aimed to describe the narratives of parents, mothers, and caregivers of children aged between 4- and 7-years about childhood sexual education within the family. For this purpose, a qualitative approach was used, conducting semi-structured interviews that addressed three main categories: childhood sexuality, childhood sexual education, and family communication. The findings showed that childhood sexual education, from the families' narratives and experiences, focuses on prevention, hygiene, and body care, presenting a view of childhood sexuality centered on biological and sociocultural aspects that look to assign minors to roles, stereotypes, and gender expression